Simulation of water resources carrying capacity of the Hangbu River Basin based on system dynamics model and TOPSIS method - Liu, Yang; Gao, Cheng; Ji, Xiaomin; Zhang, Zeyi; Zhang, Yuquan; Liu, Chenwei; Wang, Zhenxing (Frontiers in Environmental Science, 2022)
Water resources play a key role in development. The research on water resources carrying capacity (WRCC) is helpful to judge the development status and provide suggestions for regional policy-making. In this study, the System Dynamics (SD) model and the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) method are combined to calculate the change of WRCC of the Hangbu River basin from 2015 to 2035 under four development scenarios. The results show that WRCC of each scenario decreases first and then increases. The scenario that prioritizes water resources is the best for the Hangbu River Basin, under which the WRCC will increase to 0.631 in 2035, achieving a good level. This is different from other WRCC studies. Through analysis, the research method and the development level and focus of the study area may be the reasons for this difference. In addition, some suggestions were provided such as focusing on improving the efficiency of irrigation water use and looking at the long-term development of the region.